New or amended data on Mediterranean Amphipoda: genera Dexamine, Ericthonius and Stenothoe - Krapp-Schickel, T. (Zootaxa, 2013)
The Mediterranean amphipod species Dexamine filiola n. sp. and Ericthonius didymus n. sp. were discovered by their ovigerous females which differ in length from morphologically similar species. An error in the description of Stenothoe dollfusi Chevreux could finally be cleared up, and the Mediterranean material called Stenothoe gallensis Walker in reality belongs to Stenothoe cattai Stebbing.